Slurry Synthesis and Thin-Film Fabrication Toward Production of Li₂O-B₂O₃-Al₂O₃-Based Multilayer Oxide Solid-State Batteries for Internet of Things Applications - Jihyun Park; Jongmin Choi; Jihye Seo; Wolil Nam; Soobeom Lee; Seungchan Cho; Kyungchul Park; Geonhyoung An; Beomkyeong Park; Moonhee Choi (Micromachines)
Developing thin-film sheets made of oxide-based solid electrolytes is essential for fabricating surface-mounted ultracompact multilayer oxide solid-state batteries. To this end, solid-electrolyte slurry must be optimized for excellent dispersibility. Although oxide-based solid electrolytes for multilayer structures require sintering, high processing temperatures cause problems such as Li-ion volatilization and reactions with graphite anodes. Thus, low-temperature sinterable oxide-based solid-electrolyte materials should be devised. We successfully developed the conditions for producing thin films from 21 μm thick solid-electrolyte sheets of Li2O-B2O3-Al2O3, one of the most promising candidates for multilayer solid-state batteries. A comprehensive analysis of the fabricated thin films included X-ray diffraction (XRD) to confirm their amorphous structure, scanning electron microscopy (SEM) for particle morphology, and contact angle measurements to verify surface hydrophilicity. Evaluation of a 32-layer bulk sample of solid-electrolyte sheets revealed an ionic conductivity of 2.33 × 10−7 S/cm and charge transfer resistance of 100.1 kΩ at a sintering temperature of 430 °C. Based on these results, cathode and anode active materials will be applied to develop high-energy-density multilayer ceramic batteries with hundreds of layers in future work.